A Modular Synthesis of 2-Alkyl- and 2-Arylchromans via a Three-Step Sequence - Orr, Robert K.; Campeau, Louis-Charles; Chobanian, Harry R.; McCabe Dunn, Jamie M.; Pio, Barbara; Plummer, Christopher W.; Nolting, Andrew; Ruck, Rebecca T. (Synthesis, 2017)
A convergent three-step method for the synthesis of 2-substituted chromans is described. These results have been accomplished via the Heck coupling of readily accessible allylic alcohols and 2-iodophenols, followed by reduction and Mitsunobu cyclization. The utility and generality of this method is demonstrated through the synthesis of a series of 2-aryl-, 2-heteroaryl- and 2-alkylchromans, as well as an azachroman derivative. The asymmetric version of this approach via a Noyori-catalyzed ketone reduction and subsequent cyclization is likewise highlighted.
Keywords: asymmetric synthesis; chromans; catalysis; Heck reaction; Mitsunobu reaction; heterocycles